Low‐Temperature Hydrogen Formation During Aqueous Alteration of Serpentinized Peridotite in the Samail Ophiolite. Issue 6 (21st June 2021) - Ellison, Eric T.; Templeton, Alexis S.; Zeigler, Spencer D.; Mayhew, Lisa E.; Kelemen, Peter B.; Matter, Juerg M.
Abstract: Serpentinized peridotite is reacting with groundwater in the subsurface of the Samail ophiolite in Oman. Although these rocks are partially to completely serpentinized, they interact with a groundwater aquifer containing hyperalkaline fluids rich in H2 and CH4 . Since the mechanisms by which H2 production may continue at low temperatures (<50°C) are not fully understood, core recovered during the Oman Drilling Project provides an excellent opportunity to study the mineralogy and Fe speciation in highly serpentinized harzburgite recording multiple stages of water/rock interaction. In Hole BA3A, early hydration of olivine and pyroxene, which likely occurred at temperatures of ∼100°C–200°C, produced serpentine, Fe‐rich brucite, awaruite, and little magnetite. Notably, Fe‐rich brucite is only preserved at >∼100 m depth in the core. Fe‐rich brucite is nearly absent within two near‐surface reaction zones where later stages of reaction are recorded, which include replacement of Fe‐rich brucite by Fe(III)‐bearing serpentine, and increases in the proportion of other Fe(III)‐bearing phases such as magnetite and hydroandradite. Thus, Fe‐rich brucite at depth represents substantial stored capacity for H2 production that can continue at low temperature, even after primary olivine and pyroxene are exhausted, thereby sustaining habitable conditions for microbial life. Plain Language Summary: When ultramafic rocks from Earth's mantle come into contact with water, they undergo a set of hydration reactions leading to the formation of secondary minerals such as serpentine and brucite. Such "serpentinization reactions" also often involve the oxidation of iron, which can result in the production of hydrogen gas. Many models predict abundant hydrogen production at high temperatures >250°C, but the potential reactions that may produce hydrogen are more enigmatic at lower temperatures. Using rock cores drilled from the Samail ophiolite in Oman, we show that in highly serpentinized rocks in contact with hyperalkaline, low‐temperature, hydrogen‐rich fluids, multiple stages of reactions can be observed. By analyzing changes in mineralogy with depth, it is possible to identify reaction fronts where rocks that initially formed abundant Fe(II)‐bearing minerals such as brucite are now interacting with modern groundwaters at low‐temperature to form Fe(III)‐bearing minerals including magnetite, hydroandradite, and Fe(III)‐bearing serpentine. These reactions are likely responsible for the production of hydrogen gas that is able to support a rock‐hosted microbial community, and show that habitable conditions can be produced even during late, non‐hydrothermal stages of ultramafic rock alteration. Key Points: Subsurface serpentinites from the Samail ophiolite contain distinct reaction fronts with implications for H2 production and habitability Where Fe(II)‐rich brucite is present, it has the potential to fuel future H2 production Fe(II, III)‐rich serpentine, hydroandradite, and magnetite all record past H2 production at low temperatures <200°C